(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
The paper considers the influence of ultrasonic fields on the photoelectric and spectral characteristics of diffusion Si-n-p receivers of electromagnetic radiation. It was found that ultrasonic irradiation increases the lifetime, diffusion length of carriers and, as a consequence, increases the efficiency of collecting carriers on the electrical contacts of Si-n-p-receivers. As a result of these processes, an increase in the value of the short-circuit current is observed, which causes an increase in the no-load voltage and the efficiency of such a diffusion Si-n-p-structure operating in the photo reformation mode.